Energy 4.0: challenges and enablers of digital twin application in power plant - Mohd Irwan Shah, Balbir Shah; Juraiza Ishak, Asnor; Hassan, Mohd Khair; Norsahperi, Nor Mohd Haziq (Penerbitan UTM Press, 2024)
Digital twins have recently garnered attention as digital solutions in "Energy 4.0" that will reshape the future of the power generation industry toward the digitalization era. It is supported by the rapid advancement of data connectivity and computational power that intensifies the potential of the digital twin approach in addressing the energy trilemma. Despite its popularity, the preliminary analysis revealed a lack of publications discussing the implementation of digital twins in the power generation industry. The researcher may find the difficulties and face the issues that prevent them from exploring this study area. Therefore, this article will perform a literature review of the selected publications to analyze the challenges and enablers of the digital twin implementation in power plants. The selection of articles from multiple databases is refined based on keywords search, publication time frame, and inclusion criteria. The study found that the challenges can be divided into nine categories, and eight enablers have been identified to address the issues that arise in digital twin applications. The findings contribute to the body of knowledge on digital twin applications by proposing the operational ecosystem framework to illustrate the interaction between enablers and challenges.